USING FLASH ANIMATION TO IMPROVE STUDENTS’ MOTIVATION IN NARRATIVE TEXT READING CLASS - Hakim, Abdul; Marbun, Rismaya; suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research was conducted based on the problem that found in teaching and learning process. From the observation in the pre-research, it was found that the students were uninterested in learning reading in English subject. The researcher did the appropriate way to overcome the problem. The researcher did a classroom action research (CAR) and tried flash animation to improve students motivation in especially reading narrative text. The participants of this research were 31 students on the tenth of class B. The research was conducted through classroom action research in two cycles. The research used observation checklist, field note, and questionnaires to collect the data. The use flash animation show that the students? motivation slightly improve. The class became relax, enjoy and easily controlled by the teacher. As the results, the students' motivation improved by using the flash animation media. The results of questionnaires also showed that with questions that given the average of students agreed that the flash animation improved their motivation. The students mean score also showed 52 that categorized average to good. The teacher also agree that students problem in motivation was solved by used flash animation. In conclusion, flash animation improved students? motivation in learning reading narrative. Keywords: Flash Animation, Motivation, Narrative Text, Reading Comprehension.